Balinese Cuisine as an instrument in Driving Gastrodiplomacy in Australia - Rumadana, I Made Rumadana; Winata, Gede Adi Sistha (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
This study investigates the potential of Balinese cuisine—specifically Ayam Betutu and Sate Lilit Ikan—as instruments for advancing Indonesia’s gastrodiplomacy efforts in Australia, particularly within the framework of the "Indonesia Spice Up the World" initiative. Recognizing Bali’s global tourism appeal and the dishes’ alignment with priority Indonesian spices, the research aims to identify how traditional foods can be culturally adapted without losing authenticity. A qualitative descriptive method was employed, involving interviews, observations, organoleptic (sensory) tests, and documentation to assess these dishes’ acceptability and market fit in Australia. The findings reveal that the modified versions of both dishes maintain their traditional texture, appearance, and aromatic identity while successfully reducing spiciness to suit Australian preferences. These culinary adjustments, when paired with beer—a common element in Australian dining culture—enhance the dishes’ acceptance as gastro-diplomatic tools. Additionally, the growing presence of Indonesian restaurants, support from diaspora communities, and government initiatives provide strong platforms for culinary diplomacy. The research implies that food modification and localized marketing strategies can significantly enhance the global impact of Indonesian cuisine, offering insights for future gastrodiplomacy policies and food export strategies.